2017
DOI: 10.1186/s12885-017-3725-3
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in PGC1α expression levels are involved in colorectal cancer risk: a qualitative systematic review

Abstract: BackgroundColorectal cancer (CRC) is a major global public health problem and the second leading cause of cancer-related death. Mitochondrial dysfunction has long been suspected to be involved in this type of tumorigenesis, as supported by an accumulating body of research evidence. However, little is known about how mitochondrial alterations contribute to tumorigenesis. Mitochondrial biogenesis is a fundamental cellular process required to maintain functional mitochondria and as an adaptive mechanism in respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…In our experiments, PGC1α knockdown reduced the ATP content and the MMP in H1299 cells. This is consistent with the study of Alonso-Molero et al on colorectal cancer, which demonstrated that decreased levels of PGC1α reduced the MMP, thus reducing chemotherapy resistance ( 39 ). A study by Do et al using breast cancer MCF-7 cells found that decreased PGC1α expression rendered cells susceptible to oxidative stress damage by suppressing NRF2 ( 40 ).…”
Section: Discussionsupporting
confidence: 92%
“…In our experiments, PGC1α knockdown reduced the ATP content and the MMP in H1299 cells. This is consistent with the study of Alonso-Molero et al on colorectal cancer, which demonstrated that decreased levels of PGC1α reduced the MMP, thus reducing chemotherapy resistance ( 39 ). A study by Do et al using breast cancer MCF-7 cells found that decreased PGC1α expression rendered cells susceptible to oxidative stress damage by suppressing NRF2 ( 40 ).…”
Section: Discussionsupporting
confidence: 92%
“…An article in a literature review article [54], aimed at evaluating whether increased or decreased peroxisome proliferator-activated receptor gamma coactivator 1-α (PPARGC1A or PGC1α) expression affects the development of colorectal cancer, found that an altered expression of PGC1α modifies colorectal cancer risk and mitochondrial biogenesis is regulated by PGC1α. According to this study, it seems plausible that the proposed algorithm found a relationship between the mitochondrial biogenesis pathway and colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they emphasize the importance of the PGC family not only in functions related directly to the mitochondria but also in those indirect functions concerning cellular metabolic activity, emphasizing that the dysfunction in the PGC family can be the basis of pathologies such as cancer. This finding is reinforced by the works of Luo and colleagues (45) and Alonso-Molero and colleagues (48), which also highlight the importance of identification of various pathways regulated by the PGC-1 family as well as the different components that are influenced and affected by it.…”
Section: Pgc-1amentioning
confidence: 84%